Selection of Optimal Traffic Signal Cycle Using Graphs - Pašagić, Husein; Mikulčić, Ivan; Marijan, Ante (Promet - Traffic&Transportation, 2012)
The paper deals with the traffic management of a traffic signal-controlled intersection. One set of movements consists ofall the possible streams at an intersection that occur simultaneously.The set of movements changes cyclically during thecontrol cycle. Within a cycle, each stream has to get at leastonce free passage, effective green time. Each set has to definethe traffic flow at the intersection with no crossing points(points of conflict). In the cyclical order of the set of movements,the intersection capacity is greater if the number of setswithin the cycle is lowe1; and 'overlapping' between the setsgreater. Using graph the01y, two intersections in the city ofZagreb have been analysed: Dubrovnik Avenue - VeeeslavaHoljevcaAvenue (6ltraffic accidents a year) and Savska Road- Street of the City of Vukovar (36 traffic accidents a year).